Adult height after treatment of neurosecretory dysfunction and comparison to idiopathic GHD. (13th October 2021) - Binder, Gerhard; Hähnel, Julia; Weber, Karin; Schweizer, Roland
Abstract: Objective: Neurosecretory dysfunction (NSD) causes growth hormone deficiency (GHD). Data on adult height after recombinant human growth hormone (rhGH) treatment are lacking. Design and Patients: We collected treatment data of all patients with NSD seen between 1990 and 2017 at our outpatient department (tertiary centre) and measured adult height. For comparison, patients with idiopathic GHD were used. Diagnoses were based on short stature (<−2 standard deviation score [SDS]), continuously low height velocity (<25th percentile), delayed bone age (by >1 SD) and low serum IGF‐1 concentration (<−2 SDS). NSD was defined by normal GH challenge results, but subnormal spontaneous GH secretion. Exclusion criteria were no information on adult height, underweight and other short stature disorders. Results: Out of 67 patients diagnosed with NSD, six were still growing, 31 had test results exceeding validated GH cut‐offs and three had other disorders causing short stature. Out of the 25 eligible patients with NSD, 21 could be recruited. These patients reached an adult height of −0.85 SDS (mean); 0.34 SDS below midparental height. Height gain during treatment was 2.01 SDS. This outcome was not different to 32 patients with idiopathic GHD. Conclusions: Long‐term results suggest the viability of the diagnosis of NSD and the efficacy of rhGH treatment.